Corrigendum "Tamno crvena grinja Tetranychus ludeni Zacher (Acari:Tetranychidae)-nova štetočina u Srbiji - Marić, Ivana; Međo, Irena; Marčić, Dejan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The original published version of the article contained two errors:(1)  In Table 1B: tomato was not indicated as host plant for T. evansi(2)   In Figure 1: After carefully looking at the previously drawings of T. ludeni body parts, we concluded that it is necessary to give new, more precise drawings  of male aedeagus and female tibia/tarsus I
Keywords: -